PENGARUH KECERDASAN EMOSIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATING - Pramono, Agus -; Suddin, Alwi - (Universitas Slamet Riyadi, 2011)
ABSTRACT The research is conducted to analysis the significance: (1) emotional intelligence toward teachers’ performance, (2) organizational commitment toward teachers’ performance, and (3) organizational commitment toward teachers’ performance SMP Kristen, SMK Kristen and SMA Kristen of Purwodadi with working motivation as moderating variable. The population is the teacher’s SMP Kristen, SMK Kristen and SMA Kristen of Purwodadi is 62 persons. Sample is all teachers’ that is 62 persons. The technique of the collecting with documentation, interview and questioner. The analysis technique data is multiple linear regressions, test of accuracy model, test of determinacy coefficient and of regression with absolute difference model. The results showed the influence of Emotional Intelligence (X1) toward Teachers’ Performance (Y) with Working Motivation (X3) as variable of moderating where Working Motivation variable will strengthen influence of Emotional Intelligence toward Teachers’ Performance. Influence of Organizational Commitment (X2) toward Teachers’ Performance (Y) with Working Motivation (X3) as moderating variable where Motivation variable will strengthen influence of Organizational Commitment toward Teachers’ Performance. Keyword: Emotional Intelligence, Organizational Commitment, Teachers’ Performance, Working Motivation.